Massive hemopericardium due to overanticoagulation in a patient with mechanical valve prothesis: Case Report - Custodio-Marroquín, Jesús Alonso (2021)
Background: Massive pericardial effusion represents less than 2% of cardiac surgery complications. Case Report: Male, 31 years old, with mechanical mitral valve, who were readmitted three weeks after cardiac surgery, due to massive hemopericardium and INR of 6,23. He underwent the pericardial window through the left mini-thoracotomy, draining 1500ml. Conclusions: It is necessary a systematic monitoring to maintain desired anticoagulation values and to identify possible complications early.